Answer:
❌
Step-by-step explanation:
If (x-a) is a factor of a polynomial then the polynomial must equal zero .
Here's what I mean :
x - 2 = 0
x = 2
(2)³-2(2)²+2(2) + 3 = 0 ❌
8 - 8 +4 +3 = 0 ❌
7 = 0 ❌
Hope this helped and have a good day
Hello,
one of two<span> fixed points inside an ellipse from which the </span>sum<span> of the </span>distances<span> to any point on the ellipse is constant. </span>
Three million, one hundred and fifty two thousand, three hundred and eight.
Answer:
4x + 4
Step-by-step explanation:
F(x) = 2x - 1
G(x) = 3x + 2
H(x) = x²
We have to calculate the expression F(G(x)) - F(x)
F(G(x)) means the composition of functions F(x) and G(x). In order to find F(G(x)) we have to replace ever occurrence of x in F(x) with the value of G(x). So,
F(G(x)) = 2(3x+2) - 1 = 6x + 4 - 1 = 6x + 3
Thus,
F(G(x)) - F(x) = 6x + 3 - (2x - 1)
= 6x + 3 -2x + 1
= 4x + 4
Therefore, the expression F(G(x)) - F(x) equals 4x + 4